Die Ordnung der Affekte Frömmigkeit als Erziehungsideal bei Erasmus von Rotterdam und Philipp Melanchthon - Müller, Ralf (Historische Bildungsforschung, 2017)
In this historical study, the educational ideal of piety, which was omnipresent in the early modern period, is systematically explored for the first time and located in the context of theology, anthropology and theories of affect. In the context of the theories of affect, the concept of piety gains depth and is made fruitful for pedagogical questions. At the same time, the theories of affect of the 16th century find their legitimate place in theological anthropology. The author analyses the foundations on which the education of affects was based in the Christian confessional context of the 16th century. The potential for emancipation becomes just as visible as immanent (self-)optimisation and pressure to conform. Two of the most important protagonists of 16th century pedagogy are examined: Erasmus of Rotterdam and Philipp Melanchthon. At the same time, the confessional differentiation of the pedagogy of piety and the regulation of affect is brought into view. Here, the study brings to light decisive differences rooted in the respective anthropologies. The work opens up the foundations for research into piety from a pedagogical perspective. Piety appears as a multi-layered concept with great potential for understanding the pedagogy of the 16th and 17th centuries.